Quantitation of certolizumab pegol by validated liquid chromatography methods - Clóvis Dervil Appratto Cardoso Júnior; Bruna Xavier; Rafaela Ferreira Perobelli Dumoncel; Francielle Santos da Silva; Sérgio Luiz Dalmora (Universidade de São Paulo, 2023)
Abstract Certolizumab pegol (CZP) is a Fab' fragment of the humanized antibody with anti-TNF-α activity that is indicated as therapy for Crohn's disease and rheumatoid arthritis. Using a BioSep-SEC-S3000 column (300 x 4.6 mm i.d., 5 µm particle size), a size exclusion liquid chromatography (SEC) method was developed. Mobile phase A consisted of 100 mM monobasic sodium phosphate and 200 mM sodium chloride (pH 7.0), while mobile phase B was ethanol (95:5, v/v), and the analysis was performed using a diode array detector (DAD) set to 214 nm and a flow rate of 0.5 ml min-1. In addition, a reversed-phase liquid chromatography (RP-LC) method based on gradient elution was developed on a Zorbax 300 SB C18 column (150 mm x 4.6 mm i.d., 3.5 µm particle size) kept at 80 °C. Mobile phase A was 0.1% (v/v) TFA in ultrapure water, and mobile phase B was a mixture of propanol, acetonitrile, ultrapure water and TFA (70 + 20 + 9.9 + 0.1, v/v) operated at a flow rate of 1.0 ml min-1, and DAD was applied at 214 nm. CZP elution was achieved with retention times of 5.6 min and 9.0 min for SEC and RP-LC, respectively.